Anticoagulant residues associated with an attempted rodent eradication from a subtropical coral atoll - Carmen C. Antaky; Israel L. Leinbach; Jonathan H. Plissner; Elizabeth N. Flint; Amanda S. Adams; Wesley J. Jolley; Benjamin G. Abbo; Hayden Hamby; Shane R. Siers; Steven C. Hess (PLoS ONE, 2026)
The use of rodenticides is a primary method for eradicating rodents from islands for conservation purposes. Rodenticide residue monitoring is often incorporated into rodent eradication project planning to understand the potential effects on nontarget species, but robust long-term sampling is often challenging due to logistical and financial constraints. We documented more than two years of rodenticide residues at fine-scale intervals with over 570 samples associated with a rodent eradication attempt. Brodifacoum-25D Conservation was applied in an attempt to eradicate house mice ( Mus musculus ) from Midway Atoll National Wildlife Refuge in the Northwestern Hawaiian Islands. As a cooperating agency, USDA National Wildlife Research Center collected and tested environmental samples for brodifacoum residues, targeting compartments (invertebrates, vertebrates, water, soil, and plants) that may affect the health of humans and wildlife. Brodifacoum residues in invertebrates peaked immediately after bait application and persisted in low levels until becoming undetectable nine months after bait application. Brodifacoum residues decreased over time but persisted in some vertebrate species (geckos, fish, birds) throughout the one-year sampling period after bait applications. All soil and water environmental samples had either no detectable residues or were under method limit of quantitation. No detectable residues were found in drinking water systems or food plant samples. The adaptive environmental monitoring, which included rapid turnaround of analytical chemistry results, enabled real-time management decisions for nontarget species, mitigation approaches, and community action.